Inequity in Australian health care: how do we progress from here? - Gavin Mooney (Elsevier, 2003)
Abstract Objective:To determine some of the key problems in pursuing equity in Australian health care and to identify some of the ways of overcoming these problems, particularly in Aboriginal and Torres Strait Islander health care. Methods:To identify and debate the key equity issues particularly related to Aboriginal and Torres Strait Islander health care but also with respect to public versus private and rural/remote versus metropolitan. Results:Political leadership and political will plus a more compassionate, less complacent society are crucial. Conclusions and implications:Political leadership is needed that can inspire a more compassionate society and which reflects better the informed values of the Australian people, adopting a communitarian paradigm. There is a need for a 'health care constitutional convention' to allow the values of the populace with respect to equity to be elicited and to ensure that voices of the disadvantaged are heard. In the specific context of Aboriginal and Torres Strait Islander health care, there is a need first to recognise and thereafter break down the racism that exists in many Australian institutions.